Textile market : clothing industry facing new challenges - Gavranović, Ante (Array, 2020)
Fashion has serious economic, environmental and social effects. McKinsey’s Global Fashion Index states that over a hundred billion pieces of clothing are produced annually. A Greenpeace study shows that in Germany, for example, 60 new garments are bought per person per year. The production, transport and use of goods (washing, drying, ironing) cause more than 850 million tons of CO2 emissions each year. In short, it is an industry that is seriously damaging the environment. The fall in clothing prices in the last 20 years has enabled the purchase of an increasing number of garments. Analyses show that now, on average, we have five times more clothes than our grandparents had. This favourable trend in spending, however, also has its flip side of the coin: we feel great until we discover what is actually hiding behind this trend. In reality, this continuous accumulation of cheap clothes is possible only due to the constant reduction of production costs. This, in turn, has very serious consequences for our health, our planet, but also for the life and economic position of workers in the clothing and textile industry as a whole.